Outdoor Learning to Improve the Wetland Ecological Literacy of Geography Education Students - Faisal Arif Setiawan; Aswin Nur Saputra (Geosfera Indonesia, 2022)
Some geography education students score poorly in wetlands ecological literacy. This study aimed to determine the effect of outdoor learning on wetlands ecological literacy using a pre-experimental design and a sample of 60 geography students. The wetlands ecological literacy instruments were adapted from Anderson's cognitive dimensions comprising factual, conceptual, strategic, and metacognitive indicators. Data were analyzed using percentages and non-parametric Wilcoxon ranked statistical sign tests. The result showed that 2-tailed Asymp. Sig. was 0.000, smaller than 0.05. The conceptual and metacognitive indicators had the highest and lowest improvement of 21.11% and 13.33%, respectively. Furthermore, students’ wetlands ecological literacy improved through outdoor learning. Outdoor learning increases students’ attention to their environment through closer interactions, complementing the learning experience. Therefore, outdoor learning improves students’ wetland ecological literacy. Keywords : Outdoor learning; ecological literacy; teacher candidate; wetlands Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License